Acyliridium(III) Complexes with PCN Terdentate Ligands Including Imino‐ or Iminium‐Acyl Moieties or Formation of Hydrido from Hydroxyl. Issue 12 (April 2016) - Zumeta, Itziar; Mendicute‐Fierro, Claudio; Rodríguez‐Diéguez, Antonio; Seco, José M.; Garralda, María A.
Abstract: Invited for the cover of this issue is the group of María A. Garralda at Universidad del País Vasco, San Sebastián, Spain. The cover image shows an anionic dihydridoiridium species formed in methanol from a dihydridoirida‐β‐diketone and hydrogen release from the dihydrido species upon addition of 2‐aminoalkylpyridines to the solution. Hydrogen is transferred from hydroxyl in the solvent to iridium to afford the final hydridoaminodiacyl species. Abstract : We find it most exciting that, in the presence of amines, a hydrido complex forms by transfer of the acidic proton in the alcohol solvent to the metal... Read more about the story behind the cover in the Cover Profile and about the research itself onp. 1790 ff .